Burnout syndrome and wellbeing in anesthesiologists: the importance of emotion regulation strategies - Lapa, TA (2017)
Anesthesiologists face stressful working conditions that can culminate in burnout syndrome. Despite various studies and protective measures which have attempted to prevent this situation, burnout continues to be a problem within the profession, impacting negatively on physicians' lives and their performance. In this review article mechanisms and consequences of burnout are described in addition to individual strategies for stress management and burnout reduction with potential impact on health care quality and wellbeing in anesthesiologists. Organizational strategies appear to have an important role in burnout reduction but need to be used in conjunction with individual programs. The latter are essential to both reducing stress and burnout in anesthesiologists and improving happiness and wellbeing. New measures of emotion regulation strategies such as mindfulness, self-compassion, resilience and empathy promotion have been shown to be approaches with substantial supporting evidence for reducing burnout and improving stress management. The evaluation and implementation of these self-regulatory competencies is a challenge. Further research is necessary to identify which programs will best suit the needs of anesthesiologists and to measure their effects on patient care and health care system quality.